The Relationship Between Self-Regulation and Fear of Missing Out in Adolescent Social Media Users in RW.05 Penggilingan Jakarta - Virlyana, Adinda; Arfian (Insight School Academy, 2025)
Introduction to The Problem: There is a phenomenon of individuals who feel afraid that they will be left behind if they do not use social media regularly, both during their activities and in their free time. On the other hand, those who feel satisfied when using social media and getting the information they want. Selfregulation is a person's ability. Purpose: This research aims to determine the relationship between selfregulation and fear of missing out among adolescent social media users in RW.05, Penggilingan Village, Jakarta. Design/methods/approach: This research method uses quantitative methods with a sample of 179 teenagers aged 12-18 years who actively use social media and the data is analyzed using the correctional product moment method from Person. Findings: The research results show that there is a significant positive relationship between self-regulation and fear of missing out with a correlation value of 0.326 and a significance value of 0.001 (p < 0.05). This research succeeded in finding that there is a significant relationship between self-regulation and fear of missing out among adolescent social media users in RW.05, Penggilingan Village, Jakarta. The direction of the relationship obtained between these two variables is positive. A positive relationship means that if self-regulation is high, it will be followed by a high fear of missing out, and vice versa, the lower the self-regulation, the lower the fear of missing out. Research implications/limitations: none Originality/value: none.